Effects of Essential Oils for Broiler Chicks with Delayed Feeding after Hatching 2. Morphological Development of Small Intestine - Senay Sarıca; Menderes Suicmez; Muzaffer Corduk (Turkish Journal of Agriculture: Food Science and Technology)
The study investigated the effects of oregano- or red pepper-essential oil at delayed feeding (0, 24 and 48 h post-hatching) on performance and morphological development of small intestine segments. Female broilers were fed one of 3 rations including a control ration with no essential oil (CONT), the rations added with either oregano essential oil (OEO) or red pepper essential oil (RPEO) at 250 mg/kg to CONT. A total of 18 chicks from each treatment were used to measure the morphological parameters of the small intestine segments on the 14th day. Prolongation of accessing time to ration significantly decreased the body weights of broilers at 3rd, 7th and 14th d, feed intake (FI) from 4 to 7 d and improved feed conversion ratio (FCR) of broilers at the period of 4-7 d. Access to ration for 48 h post-hatching significantly decreased the body weight gains at the period of 4-7 and 7-14 d, FI from 7 to 14 d and improved FCR of broilers at the period of 7-14 d. OEO250 ration significantly increased villus height (VH) and villus surface area (VSA) of jejunum (J) and ileum (I) of broilers fed immediately and the IVH and IVSA of broiler accessed to ration for 48 h post-hatching. VH of duodenum (D), IVH and IVSA of broilers fed for 24 h post-hatching were significantly increased by RPEO250 ration. OEO250 and RPEO250 rations significantly reduced crypt depth (CD) of D and J of broiler accessed to ration for immediate and DCD of broiler fed for 24 h post-hatching. OEO250 and RPEO250 rations significantly increased IVH and IVSA and reduced DCD, JCD and ICD of broilers. In conclusion, OEO250 and RPEO250 rations affected positively VH and VSA of I and reduced CDs of small intestine segments of broilers accessed to ration at different times.